Pseudodementie ‘anders’: hoe stereotiepe ideeën de kans op dementie verhogen - Diesfeldt, Han F. A. (Tijdschrift voor Gerontologie en Geriatrie, 2013)
bespreking: Haslam C, Morton TA, Haslam, SA, Varnes L, Graham R, Gamaz L. “When the age is in, the wit is out”: agerelated self-categorization and deficit expectations reduce performance on clinical tests used in dementia assessment. Psychology and Aging 2012;27:778–784.